Optimizing Coal Hauling Operations: A Strategic Plan for Increased Productivity at PT Borneo - Galuh Joko; Nur Budi Mulyono (Research Synergy Press, 2023)
The purpose of this research is to determine the key operational variables that impact productivity in PT BORNEO and identify optimal targets to improve productivity. A mixed methodology of qualitative and quantitative approaches, supported by process observation, was used to collect data. The study primarily uses existing quantitative data, but interviews may be conducted to capture constraints in the implementation plan process. GPS data also collected via an API to obtain information about truck movements, which can be divided into various activities to identify cycle time and analyze system performance. The study found that reducing loading time and minimizing random stoppages can significantly improve productivity, with average loading time being the most important factor. Stoppage before rest time and stoppage in loaded condition and at major prayer time had little impact on overall productivity. Future research could investigate the impact of other variables such as equipment maintenance and driver training on productivity.